Uma prática social inerente à manifestação de cultura popular regional: análise da festa do carro de boi de Macuco de Minas - Carmo, Liliana Cristina do (2022)
This work aims to analyze the Party of Carro de Boi de Macuco de Minas as an example of social practice inherent to regional popular culture, seeking to understand how the relationships between the social actors of this event happen, as well as the importance of the party for that community. The interest in the subject arose from the rescue of my own memory, as I was born in the city of Itumirim, also my parents' land, a city for which I have extreme affection. Several times, in my childhood and youth, I heard several stories related to the party. Thus, in order to rescue and get closer to the subject, it was necessary to carry out a bibliographic research on the subject, seeking to understand the term culture and its relevance to the formation of a society and its various nuances, especially Brazilian culture. Understanding what social practices are and how they happen within a community and their importance within popular culture. The theme of this work rescues the value of a tradition in the interior of Minas Gerais: the ox cart, in particular, as an object celebrated at the Party of Carro de Boi de Macuco de Minas.